Nanoparticle mediated drug delivery of rolipram to tyrosine kinase B positive cells in the inner ear with targeting peptides and agonistic antibodies - Glueckert, Rudolf; Pritz, Christian O.; Roy, Soumen; Dudas, Jozsef; Schrott-Fischer, Anneliese (Frontiers in Aging Neuroscience, 2015)
Aim: Systemic pharmacotherapies have limitation due to blood-labyrinth barrier, so local delivery via the round window membrane opens a path for effective treatment. Multifunctional nanoparticle (NP)-mediated cell specific drug delivery may enhance efficacy and reduce side effects. Different NPs with ligands to target TrkB receptor were tested. Distribution, uptake mechanisms, trafficking, and bioefficacy of drug release of rolipram loaded NPs were evaluated. Methods: We tested lipid based nanocapsules (LNCs), Quantum Dot, silica NPs with surface modification by peptides mimicking TrkB or TrkB activating antibodies. Bioefficacy of drug release was tested with rolipram loaded LNCs to prevent cisplatin-induced apoptosis. We established different cell culture models with SH-SY-5Y and inner ear derived cell lines and used neonatal and adult mouse explants. Uptake and trafficking was evaluated with FACS and confocal as well as transmission electron microscopy. Results: Plain NPs show some selectivity in uptake related to the in vitro system properties, carrier material, and NP size. Some peptide ligands provide enhanced targeted uptake to neuronal cells but failed to show this in cell cultures. Agonistic antibodies linked to silica NPs showed TrkB activation and enhanced binding to inner ear derived cells. Rolipram loaded LNCs proved as effective carriers to prevent cisplatin-induced apoptosis. Discussion: Most NPs with targeting ligands showed limited effects to enhance uptake. NP aggregation and unspecific binding may change uptake mechanisms and impair endocytosis by an overload of NPs. This may affect survival signaling. NPs with antibodies activate survival signaling and show effective binding to TrkB positive cells but needs further optimization for specific internalization. Bioefficiacy of rolipram release confirms LNCs as encouraging vectors for drug delivery of lipophilic agents to the inner ear with ideal release characteristics independent of endocytosis.